PENGKHIANATAN ISTRI DALAM CERPEN “AN IMAGINATIVE WOMAN” KARYA THOMAS HARDY: SEBUAH KAJIAN FEMINISME PSIKOANALISIS - Yulistiyanti Yulistiyanti (Dinamika Bahasa dan Budaya, 2012)
Thomas Hardy’s An Imaginative Woman depicts woman condition in England in Victorian era (19th century). Women were oppressed in domestic and public areas because England was dominated by patriarchy. The social norms were influenced by patriarchy.Relating to the social condition found in the work, psychoanalysis feminism is applied to analyze the object. Psychoanalysis feminism by Dorothy Dinnerstein reveals gender paradigms and these paradigms are found in the work. There are inequality relation between men and women caused by patriarchal social norms. Parenting is the aim of psychoanalysis feminism. It will create androgyny generation that has feminine and masculine personalities. Key words: short-story, gender paradigm, psychoanalysis feminism, androgyny, patriarchy